Recent Publications (Quarterly Journal of Economics, 1935)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 49, Issue 2, February 1935, Pages 364–370, https://doi.org/10.1093/qje/49.2.364 Published: 01 February 1935